Dietary Epicatechin, A Novel Anti-aging Bioactive Small Molecule - Si, Hongwei; Lai, Chao-Qiang; Liu, Dongmin (Current Medicinal Chemistry, 2021)
Epicatechin (EC), a flavonoid present in various foods including cocoa, dark chocolate, berries, and tea, has recently been reported to promote general health and survival of old mice fed a standard chow diet. This is considered a novel discovery in the field of identifying natural compounds to extend lifespan, given that presumably popular anti-aging natural agents including resveratrol, green tea extract, and curcumin had failed in extending the lifespan of standard chow-diet-fed mice. However, the anti-aging mechanism of EC is not fully understood, thus impeding the potential application of this natural compound in improving a healthy lifespan in humans. In this review, we first summarized the main dietary sources that contain a significant amount of EC and recent research regarding the absorption, metabolism and distribution of EC in humans and rodents. The review is then focused on the anti-aging effects of EC in cultured cells, animals and humans with the possible physiological, cellular and molecular mechanisms underlying its lifespan-extending effects.
Keywords: dietary intake